Cultivating Future Graduate Entrepreneurs: A Holistic Exploration of Vital Entrepreneurial Skills from a Tripod-Based View and Evidence - Magasi, Chacha (SEISENSE (PRIVATE) LIMITED, 2025)
Purpose- This study aimed to examine essential entrepreneurial skills as perceived by students, practicing entrepreneurs, and employers in Tanzania, focusing on the ecosystems of Dar es Salaam and Mwanza.Design/Methodology- A qualitative cross-sectional design was employed, using stratified random sampling and purposive sampling to conduct in-depth interviews with students, entrepreneurs, and employers. Thematic analysis was used to interpret the qualitative data.Findings- The study identified ten critical entrepreneurial competencies: communication, problem-solving, adaptability, resilience, teamwork, creativity, initiative, networking, leadership, and customer focus. There was consensus among all groups regarding the importance of these skills, with students emphasizing curricula that incorporate real-world challenges, and entrepreneurs and employers stressing the need for practical experience, financial literacy, strategic thinking, innovation, and ethical decision-making.Practical Implications- The study offers recommendations for enhancing entrepreneurial education by integrating hands-on learning, internships, case studies, mentorship, and practical experience into academic programs. It also suggests a unified framework for curriculum enhancement, incorporating the perspectives of students, entrepreneurs, and employers to improve entrepreneurial education.